Anti-obesity effects of Laminaria japonica fermentation on 3T3-L1 adipocytes are mediated by the inhibition of C/EBP-Î±/Î² and PPAR-Î³ - Kim, Young-Min; Jang, Mi-Soon (Cellular and Molecular Biology, 2018)
Obesity is global problem that contributes to disease, and is partly caused by fast-food, high-fat diets. Much attention has been focused on developing anti-obesity foods and chemical materials from natural sources. Seaweed has bioactive properties that influence immune activity and have anti-cancer and anti-obesity effects. Laminaria japonica is a widely consumed seaweed, and has been promoted as a health food in Korea. The bioactive properties of L. japonica include anti-cancer, anti-diabetic, and anti-inflammation effects. Most Laminaria japonica are distributed in a simple processing form such as drying, and their availability is very low. Therefore, various types of functional products can be developed if they can be applied to foods through functionalization using fermentation techniques. It is a structural problem that is the most problematic in seaweed processing. In this study, we used fermented Laminaria japonica. To increase physiological activity, fermentation treatment was performed to loosen the structure, thereby increasing the activity of the glycoprotein. First, we screened the anti-obesity potential of an L. japonica fermentation extract (LJF) using 3T3-L1 adipocyte cells. We determined cytotoxicity using an MTS assay and measured LJF for its ability to affect adipogenesis through glucose uptake, triglyceride levels, and Oil Red O staining. We confirmed that LJF inhibited adipocyte differentiation. CCAAT/enhancer-binding proteins Î±/Î² (C/EBP-Î±/Î²) and peroxisome proliferator-activated receptor-Î³ (PPAR-Î³) are involved in the early and late stages of adipocyte differentiation. LJF significantly reduced the expression levels of C/EBP-Î±/Î² and PPAR-Î³ and decreased the concentration of adiponectin. Thus, our results suggest that LJF inhibits adipogenesis in 3T3-L1 cells, and may be valuable for its anti-obesity effects.